Juridical Review Of The Authority Of Civil Servant Investigators In Conducting Forced Searches Of Violators Of Local Regulations Based On The Provisions Of Indonesian Laws And Regulations - Solehuddin, Solehuddin (Widya Yuridika, 2024)
In this study the author discusses one of the problems regarding the authority of civil servant investigators (PPNS) in carrying out forced searches based on the provisions of laws and regulations in Indonesia. The purpose of this study is to determine and analyze the authority of civil servant investigators (PPNS) in conducting forced searches based on the provisions of laws and regulations in Indonesia and to determine and analyze civil servant investigators (PPNS) can make forced searches of perpetrators suspected of committing criminal violations of local regulations. The research method uses normative legal research, so the research approach taken is a statute approach, conceptual approach, and case approach. The results of this study are the first, the authority of civil servant investigators (PPNS) according to Indonesian legislation is regulated in the provisions of Law No. 8 of 1981 concerning Criminal Procedure Law (KUHAP) Government Regulation No. 43 of 2012 concerning Procedures for Implementing Coordination, Supervision, and Technical Guidance of Special Police, Civil Servant Investigators, and forms of Private Security, Regulation of the Chief of the Indonesian National Police Number 14 of 2012 concerning Management of Criminal Investigations, Regulation of the Chief of the Indonesian National Police Number 6 of 2010 concerning Investigation Management by Civil Servant Investigators. Secondly, the provisions of the above laws and regulations that in the event of a criminal offense in the region, civil servant investigators (PPNS) can search the perpetrator of the offense, but still the PPNS authority must be expressly regulated in the provisions of regional regulations because however PPNS in the regions must be subject to Regional Regulations that regulate their authority.